INVESTIGATION OF PARAMETERS EFFECTING OXYGEN GAS PERMEATION PROPERTIES OF POLYPROPYLENE PART-A; APPLICATION OF ARRHENIUS EQUATION TO OXYGEN TRANSMISSION RATE (OTR) OF POLYPROPYLENE AND CLAY NANOCOMPOSITES - Atayev, Parahat; Oner, Mualla (YILDIZ TECHNICAL UNIV, 2013)
In this study, the effects of temperature and humidity on oxygen transmission rates (OTR) of polypropylene and polypropylene-clay nanocomposites (PP-NC) were investigated. OTR values were found using SYSTECH Oxygen Permeation Analyser. Amounts of nanoclay (NC) added to polypropylene were 3%, 5% and 7% by weight. The analysis of the temperature dependence of OTR values of the samples showed that by increasing the temperature from room temperature (25 degrees C) to the 30 degrees C, 40 degrees C and 50 degrees C respectively, the OTR also increased in all prepared composites. The results showed that, filled polypropylene has low oxygen permeability than unfilled polypropylene. Temperature-OTR changes were applied to Arrhenius type equation. It was observed that in all samples OTR values linearly changed by changing temperature and these changes obeyed to the Arrhenius type equation as reflected by the high correlation coefficients (0.9965-0.9990). Nanocomposites containing 5 and 7 wt.% clay nanoparticles showed good oxygen barrier properties and these properties decreased proportionally by increasing temperature. Generally, in all PP-clay samples oxygen permeability rate in wet air condition was lower than oxygen permeability in dry air condition. These OTR differences were nearly negligible in PP, PP-3% NC and PP-7% NC nanocomposites. However OTR values in wet air condition is lower than oxygen permeability rate in dry air condition in PP- 5% NC sample.
Keywords: Polymer; polypropylene; nanoclay; nanocomposite; Arrhenius equation; oxygen transmission rate; Engineering